2020
DOI: 10.1037/tmb0000011
|View full text |Cite
|
Sign up to set email alerts
|

User perceptions of powered wheelchair features.

Abstract: There has been a substantial increase in recent years in the availability of powered wheelchairs and associated features. However, the psychological factors explaining feature use are poorly understood. The current study aims to explore this issue. Semistructured interviews of 15 British wheelchairs users were conducted; all had a range of disabilities and clinically prescribed seating functions. Our aim was to explore participants' perceptions in terms of engagement and use of their wheelchair technology. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Within the domain of occupations, IADL included domestic activities, community mobility and shopping. These activities were mentioned most frequently, with 30 articles commenting on how a PMD contributes to occupation participation (Auger et al, 2010;Blach Rossen et al, 2012;Borisoff et al, 2018;Bowers et al, 2020;Brandt et al, 2004;Carver et al, 2016;Corazon et al, 2019;Edwards and McCluskey, 2010;Evans, 2000;Fomiatti et al, 2014;Francisco et al, 2019;Fredriksson et al, 2020;Giesbrecht et al, 2009;Hoenig et al, 2007;James et al, 2018;Jedeloo et al, 2002;Korotchenko and Hurd Clarke, 2014;Labbé et al, 2020;Löfqvist et al, 2012;May and Rugg, 2010;Pettersson, 2014;Pettersson et al, 2016;Samuelsson and Wressle, 2014;Stenberg et al, 2016;Sund and Brandt, 2018;Sund et al, 2015;Sullivan et al, 2020;Wee and Lysaght, 2009). The x Self-report of activity levels of past 7 days and groups into 3 categories estimating metabolic equivalent of tasks Life-space assessment composite score Auger et al (2010) x Mobility habits in 5 life-space levels.…”
Section: Enabling Participation In Iadlmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the domain of occupations, IADL included domestic activities, community mobility and shopping. These activities were mentioned most frequently, with 30 articles commenting on how a PMD contributes to occupation participation (Auger et al, 2010;Blach Rossen et al, 2012;Borisoff et al, 2018;Bowers et al, 2020;Brandt et al, 2004;Carver et al, 2016;Corazon et al, 2019;Edwards and McCluskey, 2010;Evans, 2000;Fomiatti et al, 2014;Francisco et al, 2019;Fredriksson et al, 2020;Giesbrecht et al, 2009;Hoenig et al, 2007;James et al, 2018;Jedeloo et al, 2002;Korotchenko and Hurd Clarke, 2014;Labbé et al, 2020;Löfqvist et al, 2012;May and Rugg, 2010;Pettersson, 2014;Pettersson et al, 2016;Samuelsson and Wressle, 2014;Stenberg et al, 2016;Sund and Brandt, 2018;Sund et al, 2015;Sullivan et al, 2020;Wee and Lysaght, 2009). The x Self-report of activity levels of past 7 days and groups into 3 categories estimating metabolic equivalent of tasks Life-space assessment composite score Auger et al (2010) x Mobility habits in 5 life-space levels.…”
Section: Enabling Participation In Iadlmentioning
confidence: 99%
“…The need for training in the use of PMDs was highlighted by nine studies (Blach Rossen et al, 2012;Bowers et al, 2020;Edwards and McCluskey, 2010;Hoenig et al, 2007;Jang et al, 2019;Labbé et al, 2020;; Pettersson, 2014;Sund and Brandt, 2018). Hoenig et al (2007), in a study of 43 participants, identified the need for PMD training in road rules and the use of controls to help mitigate risks of accidents when using a PMD.…”
Section: Overcoming Risk Of Harm Through Power Mobility Device Trainingmentioning
confidence: 99%
See 1 more Smart Citation